Influence of Price and Product Quality on Customer Satisfaction : Study on Consumers of a Soe Company in Central Java - Siti Aisyah; Kadir Kadir; Dhea Perdana Choenraad; Adang Adang (Acman: Accounting and Management Journal, 2023)
The research aims to determine and analyze the effect of price and product quality on customer satisfaction. The object of research is the consumers of one of the BUMN companies in Central Java, with as many as 100 respondents using descriptive analysis and verification analysis methods. Based on path analysis research, price and product quality variables on customer satisfaction among consumers of one of the BUMN companies in Central Java were declared valid. Therefore conclusions and suggestions are taken into consideration about the results of this study to pay attention to price and product quality to increase customer satisfaction.